Concise encyclopedia of psychology - Corsini, Raymond J.; Auerbach, Alan J. ([S.l.] : Wiley, 1996)
The new paperback edition--now even more concise and user-friendly! Critical Praise for the Second Edition of Concise Encyclopedia of Psychology "Intended for general readers [and] professionals, this source is easy to use, very informative, and authoritative....Highly recommended."--Choice "Concise Encyclopedia of Psychology is an impressive achievement.... [It] covers an incredible breadth of subjects in a clear, authoritative manner suitable for all levels from high school students to practicing psychologists, both academic and clinical."--American Reference Books Annual "[The] contributing authors [include] some of the most influential scholars and practitioners in the field....[The] text reads fast as well as informatively, serving as a ready reference to a wide array of subjects....[It is] a resource to be savored over and over again as the need arises....a reference text without equal."--Child and Family Behavior Therapy. "Authoritative, clear, and concisely written."--Doody's Health Sciences Book Review.